2021
DOI: 10.1039/d0nr07832h
|View full text |Cite
|
Sign up to set email alerts
|

The role of ligands in atomically precise nanocluster-catalyzed CO2 electrochemical reduction

Abstract: S/Se atoms at the metal–ligand interface can play an important role in determining the overall electrocatalytic performance of Au nanoclusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 37 publications
0
47
0
Order By: Relevance
“…10b) with testing condition of neutral pH in water. With current density as an evaluation criterion, the modified Au exhibited about 7.6-fold increase, and meanwhile the NHC [206]. g Schematic illustration of amine modification on the rGO-Au composite.…”
Section: Organic Molecule-modified Aumentioning
confidence: 99%
See 2 more Smart Citations
“…10b) with testing condition of neutral pH in water. With current density as an evaluation criterion, the modified Au exhibited about 7.6-fold increase, and meanwhile the NHC [206]. g Schematic illustration of amine modification on the rGO-Au composite.…”
Section: Organic Molecule-modified Aumentioning
confidence: 99%
“…Reprinted with permission from Ref. [ 206 ]. g Schematic illustration of amine modification on the rGO-Au composite.…”
Section: Interface Engineering For Co 2 Rrmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Jin et al. synthesized atomically precise [Au 25 (XR) 18 ] − nanoclusters with the same Au 25 kernel but different protecting ligands (−XR, X=S or Se, R: carbon tail) and found that the anchoring atom (S or Se) of the ligand strongly affects the selectivity of the CO 2 RR (Figure 9 a, b) [38] . CO is the main product when S is the anchoring atom on the surface of the Au nanoclusters, while the hydrogen evolution reaction (HER) becomes more favorable with the anchoring atom of Se.…”
Section: The Roles Of the Ligand In Surface‐engineering Of Noble Meta...mentioning
confidence: 99%
“…Fortunately, ultrasmall Au-SR NPs with core size <3 nm have been made with atomic precision (called Au-SR nanoclusters, NCs), , with all particles in a sample being truly identical. In ultrasmall NPs, the surface plasmon resonance (SPR) bandwhich dominates the optical spectrum of larger Au NPsvanishes at sizes below Au 279 (SR) 84 , giving rise to a multiband spectrum due to discrete energy states in small NCs. Moreover, such atomically precise NCs can grow into single crystals for atomic structure determination by X-ray crystallography (SCXRD), providing ideal platforms for correlating the total structures and physicochemical properties. , As such, many fundamental issues such as the structural evolution (even atom by atom), assembly, isomerism, optical absorption, , excited state dynamics, , chirality, photoluminescence, dipole moments, and catalytic performance, as well as magnetism, have been studied. The magnetic properties of thiolate (SR) protected Au NPs hold promise in magnetic resonance imaging, magneto-optical data storage, recyclable nanocatalysts, etc., but the fundamentals are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%